Nonrelativistic and relativistic simple wave problems solved with Smoothed Particle Hydrodynamics. Issue 1 (1st September 2022) - Caetano, J V O; Nowacki, L S; Franção, V S; Hirayama, Renan; Pala, K P; Sola, J O; Grassi, F
Abstract: To simulate the expansion of the matter created in relativistic nuclear collisions, codes in 3+1 dimensions are used and we are developing a new one. To benchmark such codes, the Sod's shock tube is often used. A closely related problem is the one-dimensional expansion of a gas into vacuum. In this paper, we study this problem classically and relativistically with the Smoothed Particle Method and test various techniques to improve the precision and speed of the solution.